Antibacterial effect of green tea against Porphyromonas gingivalis: a literature review - Murtadha IA Alameer; Hayder R Abdulbaqi; Dinesh Martin (College of Dentistry/ University of Baghdad, 2024)
Green tea is regarded as a healthy beverage due to the biological action of polyphenols, specifically catechins. Researchers investigated the inhibitory effects of green tea (Camellia sinensis) plant on both Gram- positive and Gram-negative bacteria. Periodontitis is mainly initiated when dysbiosis of the subgingival microbiome takes place. Porphyromonas gingivalis is one of the key pathogens involved in the initiation and progression of periodontitis when its levels in subgingival biofilm overwhelm the host's immune system. It is the main pathogen that is significantly linked to severe periodontal disease. In this study, details about P. gingivalis including information about its structure, virulence factors were provided. Next, Important points related to green tea, including its active ingredients and antibacterial activity, have been clarified. Finally, the objective of this study was to demonstrate how green tea has antibacterial effects on P. gingivalis.